KESADARAN TENAGA KESEHATAN DALAM PENCEGAHAN INFEKSI NOSOKOMIAL DENGAN PERILAKU MENCUCI TANGAN - Sekar Ayu Putri; Raudina Izzah; Sabrina Putri; Apriningsih; Chandrayani Simanjorang; Riswandi Wasir (MOTORIK Jurnal Ilmu Kesehatan, 2023)
Nosocomial infections are infections that are acquired or occurred in hospitals and are still a major health problem in the world. Hospitals as complex health units require good human resource management to provide optimal health care and prevent the spread of infections. Nosokomial infections can occur due to a number of factors, one of which is low awareness of the health energy of washing hands. The study aims to find out how high the level of healthcare awareness in Indonesia is in washing hands to prevent nosokomial infections and the factors that influence them. This study uses a literature review method using 11 literature sources from Google Scholar and Garuda. The results of this study are that the majority of health workers in Indonesia have had a good awareness in washing hands with a ratio of 44% – 77.4%. The author suggests to improve and strengthen hand washing behavior for health workers.